A new approach for the grinding of Nordic skis - Breitschädel, F. (Procedia Engineering, 2015)
Stone grinding has been the state-of-the-art for Nordic ski preparation for approximately the last 2.5 decades. This paper presents a new approach to preparing ski running surfaces, and a new grinding machine has been developed. A grinding wheel made of metallic material, a stationary placed ski and fully controllable process parameters are some of the key features for this device. The processes of traditional stone grinding and the new approach with a metallic grinding wheel are presented. Two examples of both grinding methods were analysed with a 3D microscope, and amplitude and spacing parameters are presented. In a further step, a comparison between traditional stone grinding and grinding with a metallic tool was performed. A relative variability of the mean roughness of 5.1% for the metallic ground skis was clearly lower than the 8.4% for the stone ground ones, which emphasizes an improved control of the resulting surface texture with the presented new metallic grinding approach.